Social media visual framing towards political participation : an analysis on BERSIH 2.0 - Mohd Firdauz Mohd Fathir; Anitawati Mohd Lokman; Shamsiah Abd Kadir; Ismail Sualman (Penerbit Universiti Kebangsaan Malaysia, 2022)
The political atmosphere in Malaysia had witnessed a growing trend of social movement organisations and protests. The recent attention is on the phenomenal record usage of social media platforms as tools to spread political ideology. The multimodal nature of social media has made it an efficient tool where users can post textual information as well as visual materials to reach out to its audience. This article sets out to examine the visual strategy of one of the largest political social movements in Malaysia, the BERSIH movement, within a social media setting. Building on the existing work on visual framing, it asks: How were issues visually portrayed on the BERSIH social media account during the peak of the movement in Malaysia? In this context, Facebook was chosen as the social media platform analysed as it is the main social media used by the movement. Adapting on the level of visual framing, a content analysis was done to a sample of 59 (N=59) top liked photos posted on the Bersih 2.0 Official Facebook account which received more than 0.5% engagement rate (ER= >0.5%). The findings showed that at the denotative level, the main forms of visuals used were photos of protesters, followed by posters and photos of important individuals. The findings also showed that at the connotative level, the main frame highlighted was ‘solidarity’ followed by ‘call for action’ in the form of direct and symbolic visuals.